Shape memory actuated sliding mechanism for rapid switching between button-patterns for adapted human-machine interaction at different automatization levels in automobiles - Kalairaj, Manivannan Sivaperuman (2018)
Almost all electronics and mechanical equipment have controllers to control the entire or certain tasks. These controllers respond to various types of inputs and performs the function accordingly. One type of input given to the controller is the touch and these controllers which use human touch has touch screen to act as the medium. The touch screen does not give haptic feedback to the users whereas the buttons normally take up more space and cause disturbance and confusion in recognizing the state and the function of the buttons. In this paper, we propose a simple sliding mechanism for rapid switching between different button patterns, in which the buttons remain flat in the surface when inactive and protrude out of the surface when active. The design and simulation are carried out on SolidWorks and the prototypes are fabricated and tested. This mechanism incorporated in the buttons and installed in an automobile, increases the level of automation and enhances the human-machine interaction.